FISH FINGERLING IN THE CORAL REEF OF SON TRA PENINSULA, DA NANG - Vi, Nguyen Thi Tuong; Quang, Vo Van (Vietnam Journal of Marine Science and Technology, 2015)
This paper presents the survey results on reef fish fingerling in water of Son Tra Peninsula, Da Nang. The results focused on fingerling of three families: Grouper (Serranidae), Rabbitfish (Siganidae) and Snapper (Lutjanidae). They concentrate in the main season from April to September and are exploited by diving and seine net. There are 14 fish species of commercial resources, consisting of Grouper (Serranidae) - 8 species, Rabbitfish (Siganidae) - 3 species, Snapper (Lutjanidae) - 3 species. Many species with high economic value is being brought into cultivation in Vietnam as Yellow Grouper (Epinephelus awoara), Orange-spotted grouper (Epinephelus coioides), Malabar grouper (Epinephelus malabaricus), Golden Rabbitfish (Siganus guttatus) and some species have been cultured in some countries such as John’s snapper (Lutjanus johnii). The collected fingerling fish have different sizes depending on the species, ranging from 44 - 148 mm. The fingerlings have an average density of 31.5 individuals per 400 m2; including Rabbitfish (Siganus spp) with the highest density of 25.4 individuals per 400 m2, Grouper (Serranidae): five individuals per 400 m2, Golden Rabbitfish (Siganus guttatus): one individual per 400 m2, and Snapper (Lutjanidae) only 0.1 individuals per 400 m2.